Evaluation and outcome of hearing in meningitis patients - Gupta, Nandini; Khandelwal, Abhishek (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Meningitis remains the most common cause of acquired severe to profound SNHL in childhood. Likewise, deafness is the most common long-term neurological sequelae of the disease. Important consideration following meningitis is the development of labyrinthitis ossificans in which there is new bone formation within the lumen of the otic capsule. Ossification of the labyrinth can develop within a few days of meningitis which can make cochlear implantation difficult. Every newborn should be promptly screened for any hearing deficit along with the patients having meningitis. The most easily available investigation are OAE and BERA. Methods: Our ambispective study of 25 patients was undertaken in a duration of 2 years in ENT department of civil hospital, Ahmedabad. All the patients underwent a detailed clinical examination and all routine audiological, and radiological investigations. Results: The prevalence of hearing loss in post meningitis pediatric age group is 40%. Females are affected more than males. Median age group of presentation with hearing deficit is 4 years. Patients with complete immunization history have lower incidence of hearing loss associated with meningitis than incomplete immunization. Ossification of the cochlea can develop as early as 6 days from the development of first symptom. Conclusions: Ossification of the cochlea can develop as early as 6 days from the development of first symptom. These are the candidates who should be prioritized for cochlear implant surgery. Patients with mild hearing loss recovered completely whereas those with profound hearing loss underwent cochlear implant surgery and were benefited with it.